A missiological study of the role of the baptism and infilling of the holy spirit in Ghanaian Pentecostal Churches - Niemandt, Cornelius Johannes Petrus (Nelus) (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2014.